Proposta de combustível reprocessado diluído em tório para sistemas PWR - inserções homogênea e micro heterogênea - Fabiana Beghini Avelar (2016)
It was proposed, in this study, the insertion of a nuclear fuel to be used in PWR systems, considering two insertions types: homogeneous and micro heterogeneous. By using the computer software system SCALE 6.0, the study of the libraries sensibility was initially done considering the thorium insertion with two benchmarks of a fuel pin, considering two types of fuel: a MOX and a ThO2-UO2 fuel. Then, the reprocessed fuel spiked with thorium were characterized and inserted in three models: a cell, an element and a nucleus. The neutronic data evaluation was carried out by the analysis of de effective and infinite multiplication factors, as well the fuel evolution during the burnup. The conversion ratio (CR) was also evaluated for the nucleus model during the burnup for each geometry e composition proposals.The results show the possibility of the reprocessed fuel spiked with thorium insertion in a PWR system and, in neutronic terms, within this thesis analysis, the homogenous insertion showed to be more suitable than the micro heterogeneous insertion. The results also show that, when introducing this fuel in a nucleus, it is necessary to eliminate the elements which contain poison burnable, due to the huge amount of absorber material present in the reprocessed fuel spiked with thorium. Besides, the conversion ratio obtained was greater than the presented by standard fuel, indicating the possibility of extending the burnup